A historic geographic approach to the anthropic disturbance in the Bükk region - Sütő, László; Balogh, Szabolcs; Novák, József Tibor; Homoki, Erika; Rózsa, Péter (Acta Geographica Debrecina Landscape & Environment series, 2021)
This paper introduce a historical geographical study on the process of land cover transformation in the Bükk Region, which can be regarded as a two-faced area concerning its anthropogenic disturbance. Based on historic mapping that began as early as the late 18th century, a database was produced, and the data was interpreted in the context of economic and social processes that took place in the area. Results could be presented in maps using the so-called Anthropogenic Disturbance Index (ADI). These maps demonstrate the peculiar land use pattern in the Bükk Region, namely co-habitation of the significantly transformed margins and the natural or quasi-natural central part. Between them, there are linear areas of intermediate disturbance. These areas, however, due to the foundation and activity of the Bükk National Park and modification of their economic value after the change of the political system, have not increased during the last several decades; rather a re-naturalization of the landscape is aimed.